Interstitial Telomeric Motifs in Squamate Reptiles: When the Exceptions Outnumber the Rule - Rovatsos, Michail; Kratochvíl, Lukáš; Altmanová, Marie; Johnson Pokorná, Martina (PloS one, 2015)
Telomeres are nucleoprotein complexes protecting the physical ends of linear eukaryotic chromosomes and therefore helping to ensure their stability and integrity. Additionally, telomeric sequences can be localized in non-terminal regions of chromosomes, forming so-called interstitial telomeric sequences (ITSs). ITSs are traditionally considered to be relics of chromosomal rearrangements and thus very informative in the reconstruction of the evolutionary history of karyotype formation. We examined the distribution of the telomeric motifs (TTAGGG)n using fluorescence in situ hybridization (FISH) in 30 species, representing 17 families of squamate reptiles, and compared them with the collected data from another 38 species from literature. Out of the 68 squamate species analyzed, 35 possess ITSs in pericentromeric regions, centromeric regions and/or within chromosome arms. We conclude that the occurrence of ITSs is rather common in squamates, despite their generally conserved karyotypes, suggesting frequent and independent cryptic chromosomal rearrangements in this vertebrate group.
Keywords: centromera; Centromere; Animals; plazi; Telomere; Base Sequence; Nucleotide Motifs; hybridizace in situ fluorescenční; telomery; nukleotidové motivy; Reptiles; zvířata; sekvence nukleotidů; In Situ Hybridization, Fluorescence; Karyotype; karyotyp